ROLE OF ELECTRONIC MEDIA IN DISSEMINATING INFORMATION FOR LIVESTOCK/POULTRY PRODUCTION - G. A. Khan; S. Muhammad; K. M. Chaudhary (Journal of Animal and Plant Sciences, 2014)
Livestock/poultry sector is a major contributor in the context of food provision as well as backstopping of the economy of Pakistan. The paper encompasses the outcomes of a study conducted regarding role of electronic media in the dissemination of information related to livestock/poultry. The data were collected through interview schedule from 330 randomly selected farmers from Faisalabad district. The analysis of the data reveals that mobile phone appeared comparatively more prominent electronic medium for getting livestock/poultry related information in an immediate and quick manner because of its interactive nature. Precautionary measures/cure against diseases was found to be the prominent area with regard to extent of information obtained and through various electronic media and its perceived effectiveness. Livestock/poultry products, marketing, and precautionary measures/cure against diseases were reported to be the prominent future preferred areas. There is a need to revitalize the electronic media (under study) for the effective dissemination of livestock/poultry related information. It is also emphasized to focus on livestock/poultry products, marketing, and precautionary measures/cure against diseases.
Keywords: electronic media; dissemination of information; livestock/poultry production